2018
DOI: 10.1097/aci.0000000000000438
|View full text |Cite
|
Sign up to set email alerts
|

How to manage food allergy in nursery or school

Abstract: A collective effort is required to keep children with food allergies safe at school. Families, healthcare providers, and school personnel should be informed on food allergen avoidance strategies, symptoms consistent with allergic reactions and anaphylaxis, how to respond to allergic reactions, and the impact the diagnosis of food allergy may have on quality of life for affected children and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 55 publications
1
12
0
4
Order By: Relevance
“…This study found that, at baseline, school personnel had moderate self‐efficacy in FAM such as assuring a safe school setting for students with FA, co‐working with other professional and families, managing allergens avoidance, guaranteeing full participation to activities to students with FA and putting in place a personalized FA care plan. However, consistent with literature data they reported low scores in AM, especially in recognizing anaphylaxis symptoms and administering proper drugs. After the specific multidisciplinary training course, all scores improved.…”
Section: Discussionsupporting
confidence: 90%
“…This study found that, at baseline, school personnel had moderate self‐efficacy in FAM such as assuring a safe school setting for students with FA, co‐working with other professional and families, managing allergens avoidance, guaranteeing full participation to activities to students with FA and putting in place a personalized FA care plan. However, consistent with literature data they reported low scores in AM, especially in recognizing anaphylaxis symptoms and administering proper drugs. After the specific multidisciplinary training course, all scores improved.…”
Section: Discussionsupporting
confidence: 90%
“…A prevenção de riscos à exposição desnecessária aos alérgenos é um grande desafio na escola, principalmente por se tratar de um ambiente coletivo, onde há o envolvimento de muitos atores. A lavagem das mãos dos profissionais, principal atividade para a prevenção e eliminação de infecções na área de saúde (Ministério da Saúde, 2013a), baseada nas diretrizes da OMS e outras organizações internacionais, foi apontada como medida importante (Oriel & Wang, 2018) para evitar a propagação de alérgenos.…”
Section: ) Melhorar a Segurança Dos Medicamentos Utilizados Nas Reaçunclassified
“…Não estabelecer uma política radical de restrição dos alérgenos nas escolas , foi considerada uma medida de alerta, pois acredita-se que criaria uma falsa sensação de segurança na escola, pois os alérgenos continuariam entrando escondidos, e o estudante alérgico estaria mais exposto. Não se pode esquecer também de reforçar a vigilância das crianças que tem diagnóstico de alergia alimentar grave (Feuille et al, 2017;Oriel & Wang, 2018) .…”
Section: ) Melhorar a Segurança Dos Medicamentos Utilizados Nas Reaçunclassified
See 2 more Smart Citations